Mechanical properties of polypropylene copolymers composites filled with rapeseed straw - Paukszta, D.; Szostak, M.; Rogacz, M. (Polimery, 2014)
This study discusses the possibility of using polypropylene copolymer as matrix composite, because they can be processed at lower temperatures. Comparing the isotactic polypropylene (PP) with copolymer PP-b-PE, lower temperature allows avoiding the limitations related with the glass transition temperature of polypropylene. On the other hand, statistical copolymer (PP-s-PE) doesn’t have such properties like block copolymer but its clarity and optical properties are better than PP polymer. Therefore, the aim of this paper was to determine the processing conditions and compare mechanical properties of polypropylene copolymer composites containing straw of oilseed rape with unfilled material as well as composites containing straw of oilseed rape with PP matrix. Two different copolymers of PP were used. Using extrusion and injection molding technique the composites with addition of 20 wt. % and 30wt. % of lignocellulosic material were prepared. The following parameters were determined: Young’s modulus at tensile, tensile strength, elongation at maximal strength, strength at break, elongation at break, strength at yield 0,2%, Brinell hardness as well as Charpy impact strength. The performed investigations revealed that copolymer matrix has good mechanical properties and lower processing temperature in comparison to composites with polypropylene matrix, because of lower degradation of the rapeseed straw.